A Textual Discourse Analysis of Introductions in Textbooks of Humanities and Basic Sciences - Shahab, Sara; Rashidi, Nasser; Sadighi, Firooz; Yamini, Mortaza (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2020)
This study attempted to scrutinize the disciplinary and cross-disciplinary generic variations of textbook introductions in humanities and basic sciences with reference to the onion model. The data included a sample of 60 introductions (i.e. ten each from applied linguistics, sociology, and psychology within humanities, and ten each from biology, agriculture, and geology within basic sciences). Humphrey and Economou’s (2015) onion model of discourse analysis was adopted, and MAXQDA 10 software of qualitative analysis was used for coding. The findings revealed similarities and differences not only within but also between the two disciplines, which can be attributed to the nature of disciplines as well as the generically accepted conventions in each discipline. Moreover, the results of the study highlighted the predominance of descriptive and analytical phases in textbook introductions not only in isolation but also in establishing more complicated genres like persuasion and critique. The study highlights the importance of teaching which is concerned with learners' rhetorical consciousness-raising of the disciplines as well as the discipline-specific lexico-grammatical features in expert texts.